Modern Information Technologies in Teaching the Russian Language (Journal of Pedagogical Inventions and Practices, 2023)
This article considers the use of information technology in Russian language lessons. The use of technical means at various lessons has a significant impact on the organization of students' activities. Also, information technologies play a great role in the learning process, qualitatively changes the process and results of learning.